Dynamic photomask directed lithography based on electrically stimulated nematic liquid crystal architectures - Mengjun Liu; Ruizhi Yang; Zhenghao Guo; Kexu Chen; Haoqiang Feng; Han Lu; Shijian Huang; Minmin Zhang; Huapeng Ye; Lingling Shui (Nature Communications)
Abstract Lithography technology is a powerful tool for preparing complex microstructures through projecting patterns from static templates with permanent features onto samples. To simplify fabrication and alignment processes, dynamic photomask for multiple configurations preparation becomes increasingly noteworthy. Hereby, we report a dynamic photomask by assembling the electrically stimulated nematic liquid crystal (NLC) into multifarious architectures. This results in reconfigurable and switchable diffraction patterns due to the hybrid phase arising from the NLC molecular orientations. These diffraction patterns are adopted as metamask to produce multiple microstructures with height gradients in one-step exposure and hierarchical microstructures through multiple in-situ exposures using standard photolithography. The fabricated pattern has feature size about 3.2 times smaller than the electrode pattern and can be transferred onto silicon wafer. This strategy can be extended to design diverse microstructures with great flexibility and controllability, offers a promising avenue for fabricating metamaterials via complex structures with simplified lithography processes.